In response to the comment on the article "Variability in case fatality rate risk due to Covid-19 according to health services provider in Mexico City hospitals" - Carmen García-Peña; Omar Yaxmehen Bello-Chavolla; Roberto Carlos Castrejón-Perez; Luis David Jácome-Maldonado; Luis Raymundo Lozano-Juárez (Instituto Nacional de Salud Pública, 2022)
Not available